(untitled) (International Journal of Engineering and Computer Science, 2018)
In this paper, we characterize the problems and their impact on adoption. in addition, and equally importantly, we describe our experience and lessons learnt in construction of a cloud computing platform, cloud computing is a new general purpose internet-based technology through which information is stored in servers and provided as a service and on-demand to clients. In this we describe the reasons of that why people switch from traditional IT to the cloud and also discuss the characteristics and types of cloud computing. This paper describes cloud computing, a computing platform for the next generation of the Internet. The paper defines clouds, explains the business benefits of cloud computing, and outlines cloud architecture and its major components. In particular, we argue that with continued research advances in trusted computing and computation-supporting encryption, life in the cloud can be advantageous from a business intelligence standpoint over the isolated alternative that is more common today.